Analysis of Teachers' Teaching Skills in Increasing Students' Learning Motivation - Cahyani, Anisa; Bujang, Bujang; Izati, Wilrahmi; Vanessa, Anadya Diva; Andriani, Ika Noviana (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2023)
History lessons are one of the lessons that students are less interested in. Many students feel bored and not enthusiastic about learning. This happens due to many factors, including the lack of precise teaching methods and media teachers use. So students become unmotivated to learn. This condition challenges Islamic Cultural History teachers to increase students' enthusiasm and motivation to learn Islamic Cultural History. This research aims to analyze the teaching skills of Islamic Cultural History teachers in increasing students' learning motivation at the madrasah level in Indonesia. This research uses qualitative research methods with a descriptive approach. Data sources were taken from fifteen informants through in-depth interviews who were selected using techniques of purposive sampling, all informants are active students, Islamic Cultural History teachers, school principals, and curriculum representatives. All interview results were then analyzed thematically using techniques by Milles and Huberman. The results of the analysis show that firstly, there are Islamic Cultural History teachers' teaching skills that are good in increasing students' learning motivation as seen from Islamic Cultural History teachers who know and continually study teaching skills. Second, the learning planning is quite good because the Islamic Cultural History teacher has prepared learning tools as a form of learning planning before the teacher teaches. The results of this research can be used as an initial reference for future researchers in studying this problem in different contexts and issues.